The role of whole brain radiation therapy in the management of newly diagnosed brain metastases: a systematic review and evidence-based clinical practice guideline - Gaspar, Laurie E. (Springer US, 2009)
Target population This recommendation applies to adults with newly diagnosed single brain metastases amenable to surgical resection; however, the recommendation does not apply to relatively radiosensitive tumors histologies (i.e., small cell lung cancer, leukemia, lymphoma, germ cell tumors and multiple myeloma). Recommendation Surgical resection plus WBRT versus WBRT alone Level 1 Class I evidence supports the use of surgical resection plus post-operative WBRT, as compared to WBRT alone, in patients with good performance status (functionally independent and spending less than 50% of time in bed) and limited extra-cranial disease. There is insufficient evidence to make a recommendation for patients with poor performance scores, advanced systemic disease, or multiple brain metastases. If WBRT is used, is there an optimal dosing/fractionation schedule? Target population This recommendation applies to adults with newly diagnosed brain metastases. Recommendation Level 1 Class I evidence suggests that altered dose/fractionation schedules of WBRT do not result in significant differences in median survival, local control or neurocognitive outcomes when compared with “standard” WBRT dose/fractionation. (i.e., 30 Gy in 10 fractions or a biologically effective dose (BED) of 39 Gy10). If WBRT is used, what impact does tumor histopathology have on treatment outcomes? Target population This recommendation applies to adults with newly diagnosed brain metastases. Recommendation Given the extremely limited data available, there is insufficient evidence to support the choice of any particular dose/fractionation regimen based on histopathology. The following question is fully addressed in the surgery guideline paper within this series by Kalkanis et al. Given that the recommendation resulting from the systematic review of the literature on this topic is also highly relevant to the discussion of the role of WBRT in the management of brain metastases, this recommendation has been included below. Does the addition of WBRT after surgical resection improve outcomes when compared with surgical resection alone? Target population This recommendation applies to adults with newly diagnosed single brain metastases amenable to surgical resection. Recommendation Surgical resection plus WBRT versus surgical resection alone Level 1 Surgical resection followed by WBRT represents a superior treatment modality, in terms of improving tumor control at the original site of the metastasis and in the brain overall, when compared to surgical resection alone.